Slime Production, Mupirocin and other Antibiotics Susceptibilities in Staphylococci Isolated from Nasal Samples in Patients Receiving Continuous Ambulatory Peritoneal Dialysis (CAPD - Ay, Selma; Aylaz, Rukiye; Sait Tekerekoglu, Mehmet (Annals of Medical Research, 2021)
None